Effects of soil water-holding capacity and soil N-NO3− and K on the nutrient content, vigour and yield of cv. Tempranillo vine and the composition of its must and wine - José María Martínez-Vidaurre; Eva Pilar Pérez-Álvarez; Enrique García-Escudero; Fernando Peregrina (OENO One, 2023)
The aim of this study was to assess the relationships between the soil water-holding capacity (SWHC), nitrate nitrogen (N-NO3−) and extractable potassium (K) content of soil; the vine nutrient content, vigour and yield; and the quality of the musts and wines in DOCa Rioja vineyards over a five-year period (2010–2014). The SWHC, N-NO3− and extractable K content of the soil were analysed in twelve cv. Tempranillo (Vitis vinifera L.) plots. Vine yield, nutritional parameters and the K and polyphenol compounds in the musts and wines were determined. In general, both the SWHC and the soil N-NO3− content were positively correlated with the N and K content of the petiole, the shoot weight and the bunch weight, but negatively correlated with the polyphenol and anthocyanin content of the musts and wines. The K extractable content was also correlated with the K content of the petiole and with the K in the musts and wines. The SWHC, the N-NO3− and the extractable K are soil parameters which have been linked to the growth and ripening of the vine plant and to the composition of the must and wine. For DOCa Rioja agroclimatic conditions, assessment of these soil parameters would enable selecting soils that support obtaining wines of better quality.